2010
DOI: 10.1007/s00397-010-0446-9
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of MR elastomers under harmonic loading

Abstract: This paper presents both experimental and modeling studies of viscoelastic properties of MR elastomers under harmonic loadings. Magnetorheological elastomer (MRE) samples were fabricated by mixing carbonyl iron power, silicone oil, and silicone rubber and cured under a magnetic field. Its steady-state and dynamic properties were measured by using a parallel-plate rheometer. Various sinusoidal loadings, with different strain amplitude and frequencies, were applied to study the stress responses. The stress-strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
194
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(197 citation statements)
references
References 22 publications
1
194
2
Order By: Relevance
“…In our experimental study [23], harmonic loadings with various strain amplitudes ranging from 1% to 50%, and frequencies from 1 Hz to 10 Hz, were used to study dynamic properties of MRE samples. Fig.…”
Section: Dynamic Propertiesmentioning
confidence: 99%
“…In our experimental study [23], harmonic loadings with various strain amplitudes ranging from 1% to 50%, and frequencies from 1 Hz to 10 Hz, were used to study dynamic properties of MRE samples. Fig.…”
Section: Dynamic Propertiesmentioning
confidence: 99%
“…Iron particles are generally used as the filler material to fabricate MREs. Both natural rubber and silicone rubber are used as typical matrixes [11,12]. Additives are commonly used to adjust the mechanical and chemical properties or electrical performance of MR fluids [13] as well as MR elastomers [14].…”
Section: Introductionmentioning
confidence: 99%
“…The additional of stiffness element is to improve the efficiency of Kevin model under sudden loading. Built on this model, Li et al [50] developed a four-parameter viscoelastic model, as shown in figure 33. In this model, a stiffness element is in parallel with the three-parameter model.…”
Section: Rheological Modeling Of Mr Elastomer Materialsmentioning
confidence: 99%
“…Figure 33. Four-parameter viscoelastic model proposed by Li et al [50] Three-parameter model is normally used to describe the viscoelastic behavior of rubber material. The three-parameter is a combination of stiffness element and a classical Kevin model (being a stiffness element and damping element in parallel).…”
Section: Rheological Modeling Of Mr Elastomer Materialsmentioning
confidence: 99%